Moldova : Technical Assistance Report on Taking Compliance Management Further. (Policy Papers; Policy Paper ;, 2012)
This report concerns the delivery of a tax administration mission to Moldova during February 8 - 21, 2012 by the Fiscal Affairs Department (FAD) of the IMF as a component of implementing FAD's technical assistance strategy for Southeast Europe.